2021
DOI: 10.1111/os.13009
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Interventions Including Vitamin D Effectively Reduce the Risk of Falls in Elderly Osteoporotic Patients

Abstract: Objective: To evaluate the effects of different intervention measures to prevent falls in elderly osteoporotic patients.Methods: A randomized controlled trial was conducted in our outpatient ward from August 2014 to September 2015.A total of 420 patients over 60 years of age were assigned to four groups. NA VitD group took 800 mg calcium and 800 IU non-active vitamin D. P-NA VitD group took 800 mg calcium, 800 IU non-active vitamin D, and received physical exercise. A VitD group took 800 mg calcium and 0.5 μg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…In total, nine studies fulfilling the inclusion criteria were identified (total n = 1568 subjects) [ 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 52 ]. The studies were conducted in several countries, i.e., USA [ 28 , 29 , 30 , 52 ], Lebanon [ 26 , 52 ], Turkey [ 25 ], Australia [ 21 ], India [ 27 ], and China [ 24 ]. The mean age of participants ranged from 32 to 71 y, and most of them included only women [ 25 , 28 , 29 , 30 , 52 ] or mostly women [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, nine studies fulfilling the inclusion criteria were identified (total n = 1568 subjects) [ 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 52 ]. The studies were conducted in several countries, i.e., USA [ 28 , 29 , 30 , 52 ], Lebanon [ 26 , 52 ], Turkey [ 25 ], Australia [ 21 ], India [ 27 ], and China [ 24 ]. The mean age of participants ranged from 32 to 71 y, and most of them included only women [ 25 , 28 , 29 , 30 , 52 ] or mostly women [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted in several countries, i.e., USA [ 28 , 29 , 30 , 52 ], Lebanon [ 26 , 52 ], Turkey [ 25 ], Australia [ 21 ], India [ 27 ], and China [ 24 ]. The mean age of participants ranged from 32 to 71 y, and most of them included only women [ 25 , 28 , 29 , 30 , 52 ] or mostly women [ 24 ]. The minimum treatment duration was 16 weeks [ 21 ], some studies had a 6 month intervention period [ 25 , 29 ], and most studies had a 12 month [ 24 , 26 , 27 , 28 , 30 , 52 ] intervention period.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations